Role of PPARα and Its Agonist in Renal Diseases - Ching-Feng Cheng; Hsi-Hsien Chen; Heng Lin (PPAR Research)
Peroxisome proliferator-activated receptor (PPAR)-α, a member of a large nuclear receptor superfamily, plays a major role in the regulation of lipid metabolism. Recently, PPARα activation has been shown to confer additional benefits on endothelial function, kidney function, and anti-inflammation, suggesting that PPARα agonists may be good candidates for treating acute renal failure. In clinical application, PPAR-α activators, such as hypolipidemic drugs in fibric acid class, were proven to have therapeutic effects on metabolic syndrome and cardiovascular disease. This paper focuses on signaling pathways, ligand selectivity, and physio-pathological roles of PPARα in kidney diseases and the therapeutic utility of PPARα modulators in the treatment of diabetes and inflammation-induced nephropathy. Implication of new and more potent PPAR-α activators could provide important insights into the overall benefits of activating PPAR-α clinically for the treatment of dyslipidemia and the prevention of diabetic or inflammation-induced nephropathy in the future.